Left ventricular clot mysteries: A case report of vanishing left ventricular clot and role of multimodality imaging in a patient presenting with ischemic cerebrovascular stroke - Susheel K. Malani; Chigullapalli Sridevi; Digvijay Nalawade; Prakash Chaudhary; Ankit Shokeen; Gauri Maheshwari (Heart India)
Cardiovascular diseases often present clinicians with a myriad of challenges, and within this spectrum, the occurrence of left ventricular (LV) clot formation remains a relatively common phenomenon. We present a singular case that challenges conventional assumptions about LV clot formation. The patient’s clinical history, diagnostic workup, and management course converge to create a compelling narrative that not only underscores the uniqueness of this case but also sheds light on potential factors that may contribute to the diagnosis of LV clots in unexpected contexts and the usefulness of multimodality imaging in this case. Through a detailed exploration of this uncommon case, we aim to contribute to the existing body of knowledge, providing insights that may guide future clinical practice and research. By presenting this exceptional case, we hope to foster a deeper understanding of the complexities surrounding LV clot formation and its implications for patient care. We present a case of a young adult patient presented with an ischemic cerebrovascular accident (CVA). He was on treatment for that as single antiplatelet and statin. He was evaluated for young CVA by the neurology department and he was referred for cardiac evaluation to rule out the cardioembolic stroke. This case report highlights an exceptional instance of LV clot formation in a young patient without the common predisposing factors typically associated with such a condition. This case also underscores the critical role of advanced imaging techniques in identifying and managing atypical presentations of LV clots.